Community Knowledge System about Karo Oil as Traditional Medicine on Ujung Labuhan Village, Namorambe, Deli Serdang - Br Aritonang, Desi Anggryani; Puspitawati, Puspitawati (Jurnal EduHealth, 2023)
This article is the result of a study on Karo Oil as a traditional medicine, this article explains what ingredients are used in the manufacture of Karo oil, and how to make Karo Oil as well as the benefits of Karo Oil for the health of the body. This research was conducted on Jl. Ujung Labuhan, Namorambe, Deli Serdang. The type of research used is qualitative research using an ethnographic approach. Based on the results of the study, it is known that the ingredients used in the manufacture of this karo oil are ginger, pepper, kencur, shallots, and garlic.